Effect of tension on steel strip in the furnace / Nor Azni Yusoff - Yusoff, Nor Azni (2011)
Physical defects produce on steel strip due to unsuitable tension applied were identified. The effect of line speed on defect produce was analyzed and grades were recommended. To obtained the result, a steel strip with the same width of 1219 mm and manipulated thickness of 0.35 mm and 0.50 mm was run on the production line with selected tension and speed due to strip dimension. The effect of line speed applied would be observed. The defect would be identified once the strip exit the furnace. The defects were tension crease and heat crease. Both defects will cause the physical appearance of the strip damaged. In an attempt to defect reducing, skin conditioning mill rolls and tension leveler machines would be applied on the strip. Then, the strip will be graded according to its quality products after the first attempt at reducing the defect was done. Also, the root cause of tension crease and heat crease that occur on the strip were listed. Line speed did contribute to producing the defects where if the speed did not match the tension applied, creases would happen. On the other hand, if tension leveler and skin conditioning mill rolls were not applied, the strip will fluctuate. Low speed and fluctuate of speed on exit tower and entry tower will also contribute to creases formation. Finally, the strip will be graded into four groups which were downgrade, second grade, hold, and scrap.